A comunicação em Matemática na sala de aula: obstáculos de natureza metodológica na educação de alunos surdos - NEVES, Maria Janete Bastos das (Universidade Federal do Pará, 2012)
The fundamental premise of this research is to analyze teaching situations in mathematics with the content of multiplicative problems classified based on Huete and Bravo (2006) through the practice of teachers (both deaf and hearing) with deaf students, searching for indicatives of methodological obstacles that may be present in the process of mathematical communication in teaching situations involving these subjects. As a guiding for the research, we used a theoretical reference that supports the teaching-learning process for deaf children with specific emphasis on the teaching of mathematics which has “LIBRAS” (Brazilian Sign Language) as its the vehicle driving force, we tried to raise some reflections about what conditions must sustain teaching. The research is an exploratory descriptive and was conducted in a Specialized Unit in deaf education. The records were made by filming. Data were analyzed from the perspective of the didactic and pedagogic elements present in the moves of its subjects and that contributed to the obstacles or to the success of the teaching-learning process of content involved. From our analysis, we concluded that the teaching of mathematics to deaf ones requires some skills from the professional involved, namely: a broad mastery of “LIBRAS”, Mathematics, Portuguese and specific teaching strategies.